Islamic Modernism in the Perspective of Teachers and Its Implications for the Design of A Love-Based Curriculum in Madrasah Aliyah - Jalaludin Faruk Azhari; Mohammad Muchlis Solichin; Nor Hasan; Mohammad Hasan (Yayasan Zia Salsabila, 2026)
This study aims to identify the Islamic modernism thinking of Arabic teachers at MA Miftahul Ulum Al-Islamy Bangkalan, analyzing its implications for the design of a love-based curriculum. This research uses a qualitative approach with a type of phenomenology. Data were collected through semi-structured interviews, observations, and documentation, and then analyzed using Interpretative Phenomenological Analysis (IPA). The validity of the data is maintained through source triangulation, method triangulation, and member checking. The results of the study show that the Islamic modernism thinking of Arabic teachers is reflected in five main characters, namely rational orientation in understanding texts, integration of ICT in learning, acceptance of new methods without leaving the tradition of pesantren, contextualization of Arabic materials with modern life, and emphasis on developing students' communication skills. This thinking has implications for the design of a love-based curriculum in the form of strengthening learning philosophy, developing integrative and humanist teaching tools, and creating a warm, safe learning environment that supports students' academic and affective growth.